Kualitas Pelayanan Dan Peraturan Tata Tertib Perpustakaan Terhadap Kepuasan Pemustaka Di Perpustakaan Soeman Hs. - Lilis Suriani; Odor Juliana Sidabutar (UIR Press, 2019)
This study aims to determine the influence of service quality and rules of regulation on user satisfaction at Soeman Hs Library. Assessment indicators used include the ability and attitude of librarians in serving, the facilities and atmosphere of the room, instructions and means of access, information access, regulations on opening hours, services, membership, the number of books that can be borrowed, length of time borrow, satisfaction, located in Soeman Hs Library department of libraries and archives the province of Riau. This research is descriptive survey that is prioritizing the questionnaire list as a collecting data and data collected with this tool and then used as the main raw material to analysing empirical conditions of objectivity at the meticulous location. There is one population group and the sample in this study is library members with a total sample of 100. Types and data collection technique used consist of primary data collected by questionnaire techniques and interview techniques and secondary data collected using observation technique and documentation technique. While analysis technique used is the validity test, reliability test, descriptive statistical analysis, inferential statistical analysis, classic assumption test, multiple linear regression analysis, f test and t test. The results of the analysis show that service quality has a significant effect on user satisfaction in the Soeman Hs Library. Rules and regulations have a significant effect on user satisfaction in the Soeman Hs Library. The contribution of influence of the quality of service and regulations on the satisfaction of users in the Soeman Hs Library is 0,674 while the remaining 0,336 is influenced by other variables such as promotion, communication and others.